The Role of microRNAs in the Infection by T. gondii in Humans - de Faria Junior, Geraldo Magela; Murata, Fernando Henrique Antunes; Lorenzi, Hernan Alejandro; Castro, Bruno Bello Pede; Assoni, Letícia Carolina Paraboli; Ayo, Christiane Maria; Brandão, Cinara Cássia; de Mattos, Luiz Carlos (Frontiers in Cellular and Infection Microbiology, 2021)
MicroRNAs are molecules belonging to an evolutionarily conserved family of small non-coding RNAs, which act on post-transcriptional gene regulation, causing messenger RNA (mRNA) degradation or inhibiting mRNA translation into proteins. These molecules represent potential biomarkers for diagnosis, non-invasive prognosis, and monitoring of the progression of parasitic diseases. Moreover, they may provide additional information on the pathophysiology of parasitic infections and guide to strategies for treatment. The Apicomplexan parasite Toxoplasma gondii modifies the levels of microRNAs and mRNAs in infected host cells by modulating the innate and adaptive immune responses, facilitating its survival within the host. Some studies have shown that microRNAs are promising molecular markers for the development of diagnostic tools for human toxoplasmosis. MicroRNAs can be detected in human specimens collected using non-invasive procedures. Changes in the circulating host microRNAs have been associated with T. gondii infection in mice and ocular toxoplasmosis in humans. Besides, microRNAs can be amplified from samples using highly-sensitive and molecular-specific approaches such as real-time PCR. In this review, we present recent findings about the role that microRNAs play during T. gondii infection and discuss their potential use to complement and improve current diagnostic tools in toxoplasmosis.